Management of a complicated crown-root fracture using adhesive fragment reattachment and orthodontic extrusion - Matida Hamata Saito, Celia Tomiko; Guskuma, Marcos Heidy; Gulinelli, Jessica Lemos; Sonoda, Celso Koogi [UNESP]; Garcia-Junior, Idelmo Rangel; Magro Filho, Osvaldo [UNESP]; Barioni, Sônia Regina Panzarini [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Dental trauma is more common in young patients and its sequelae may impair the establishment and accomplishment of an adequate treatment plan. This paper reports a case of complicated crown-root fracture in a young adult that was treated using adhesive tooth fragment reattachment and orthodontic root extrusion. Considering the time elapsed to follow up, the fracture extension, the amount of remaining root portion and the patient's low socioeconomic status, the treatment approach proposed for this case provided good functional and aesthetic outcomes. Clinical and radiographic results after 2 years were successful. This case report demonstrates the importance of establishing a multidisciplinary approach for a successful dental trauma management.